DISTRIBUTION OF HYDROCARBONS IN PARTICULATE MATTER AND BOTTOM SEDIMENTS OF THE VOLGA DELTA - Inna Nemirovskaya (Geography, Environment, Sustainability, 2010)
Data are presented on the content and composition of hydrocarbons (aliphatic and polyaromatic) in the filtered particulate matter and in the surface layer of the bottom sediments of the Volga River and the northern shelf of the Caspian Sea. Because of transformation and precipitation of anthropogenic and natural compounds, the HC composition in particulate matter and bottom sediments undergoes changes caused by precipitation of particulate matter, varying temperatures, and mixing of fresh and saline waters. It appeared that the greatest accumulation of the HC proceeds in the region of avalanche sedimentation, and their content is independent of the grain-size type of the sediments. The anthropogenic HC (oil and pyrogenous) do not pass the marginal filter of the Volga River and do not enter the open part of the sea.